Long-term variability of ice regime characteristics in river mouth areas of the western coast of the White Sea on the background of climatic changes - V. N. Baklagin; N. I. Mahalskaya (Лëд и снег)
The paper presents results of the comprehensive study of the long-term variability of the main elements of the ice regime for the period 1955–2020 in mouth areas of the rivers Gridina, Kuzema, Pongoma,Kem, Shuya, Nizhny Vyg, Suma, Nyukhcha and Maloshuika flowing into the White Sea on its western coast (Republic of Karelia, Arkhangelsk region). The average daily air temperatureы in sites of the Stateobservation network of Roshydromet – marine hydrometeorological coastal stations Gridino, Kem and Onega - were used as initial information for this work. Information about the main characteristics ofthe ice regime (times of coming of characteristic dates of ice phenomena) of the rivers was presented by data from nine hydrological posts. The mean values of characteristics of the ice regime (average statistical dates and durations of the ice regime phases) of the rivers under consideration (except those regulated by the cascade of hydroelectric power stations). were calculated. Statistical analysis of time series of the mean air temperatures obtained for the cold season on the western coast of the White Sea and the duration of periods with ice phenomena on the above rivers made possible to reveal two quasihomogeneous periods with a turning point in 1990. This analysis shows that the temperature background in years 1991–2020 is significantly higher (by 1.4 °C) than the similar one in 1956–1990, and at the same time the average duration of ice phenomena decreased to almost two weeks (shorter by 11 days). The regression analysis allowed finding the presence of a statistically significant negative trend in the duration of ice phenomena for the whole period (1956–2020), which is −3.3 days/10 years. At the same time, the shortening of the duration of the periods with ice phenomena is due equally to both a shift in the time of the beginning of the stable ice formations towards later dates (1.6 days/10 years), and the earlier dates of the ice phenomena end (−1.7 days/10 years).